2011
DOI: 10.1038/eye.2011.232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of total homocysteine and C-reactive protein for ocular ischemic syndrome

Abstract: Background To assess diagnostic efficacy of plasma total homocysteine (tHcy) and C-reactive protein (CRP) levels for ocular ischemic syndrome (OIS). Methods In all, 87 patients with retinal vein occlusion (RVO), 955 patients with a stenosis of internal carotid artery (ICA) o90% and 159 patients with a stenosis of ICA 490% were included between 2003 and 2009. A total of 43 patients with a stenosis ICA 490% were diagnosed as OIS. Fasting tHcy, CRP, lipid profiles, creatinine were measured, and diagnostic values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…7 Previous studies have suggested that the tHcy levels is a marker of atherosclerosis. 9 Our study demonstrated high tHcy levels in the blood in patients with OIS and complete internal carotid artery occlusion. A previous study demonstrated that tHcy levels were associated with the development of OIS in patients with preexisting stenosis of the internal carotid artery.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…7 Previous studies have suggested that the tHcy levels is a marker of atherosclerosis. 9 Our study demonstrated high tHcy levels in the blood in patients with OIS and complete internal carotid artery occlusion. A previous study demonstrated that tHcy levels were associated with the development of OIS in patients with preexisting stenosis of the internal carotid artery.…”
Section: Discussionsupporting
confidence: 56%
“…A previous study demonstrated that tHcy levels were associated with the development of OIS in patients with preexisting stenosis of the internal carotid artery. 9 The sensitivity and speci city of hyperhomocysteinemia for diagnosing OIS in patients with stenosis of the internal carotid artery were 70% and 79%, respectively. 9 In patients with preexisting carotid artery diseases, elevated tHcy levels in the blood are considered a risk factor for the future development of stroke.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ocular Ischemic Syndrome the ophthalmic artery in patients with maxillofacial arteriovenous malformation [ 35 ], associated with Eisenmenger's syndrome [ 36 ], mucormycosis [ 37 ], moyamoya [ 38 ], chronic herpes simplex keratouveitis [ 39 ], strabismus fi xus convergens [ 40 ], and hyperhomocysteinemia [ 41 ]. I have also seen it develop following prolonged nonophthalmic surgeries, e.g., spinal region surgery, orbital trauma, and, in one case, following shoulder surgery in a sitting position with pressure on the eyes.…”
mentioning
confidence: 99%